2019
DOI: 10.3390/app9091858
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations on the Water Entry of Cylindrical Projectiles with Different Initial Conditions

Abstract: In this paper, coupled with Reynolds-averaged Navier–Stokes equations and ballistic equations, the numerical simulations of high-speed water entry of projectiles under different conditions have been conducted. The water-gas flow was modeled by the mixture multiphase model. The numerical results indicated that the simulations agree well with analytical solutions by two cavity models, which validates the model applied. Then the effects of variations of project length, entry angle and velocity on the entry proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Hou constructed the 6DOF numerical model by using the volume of fluid (VOF) method, the large eddy simulation (LES) approach and the Eulerian multiphase model to simulate water entry physics. Gao et al (2019) investigated the dynamics of high-speed oblique water entry of different cylindrical projectiles with different initial conditions. They showed that at shallow entry angles, the projectile hits the cavity wall and makes the cavity wall less smooth and with the increase of the entry angle, it becomes possible to provide stability for the projectiles inside the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Hou constructed the 6DOF numerical model by using the volume of fluid (VOF) method, the large eddy simulation (LES) approach and the Eulerian multiphase model to simulate water entry physics. Gao et al (2019) investigated the dynamics of high-speed oblique water entry of different cylindrical projectiles with different initial conditions. They showed that at shallow entry angles, the projectile hits the cavity wall and makes the cavity wall less smooth and with the increase of the entry angle, it becomes possible to provide stability for the projectiles inside the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Chen applied the commercial code ANSYS Fluent to simulate the highspeed oblique water entry physics. Gao et al [22] examined the dynamics of high-speed oblique water entry of different cylindrical projectiles with different initial conditions. They have shown that, at shallow entry angles, the projectile hits the cavity wall and makes the cavity wall less smooth, and as the entry angle increases, it becomes possible for the projectile to have stability inside the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of military strikes and defense engineering, structure of walls should be thick in order to reduce the local damage effect [1][2][3][4][5][6] caused by projectile impacts, especially for structures requiring high-defense protection such as important fortifications and secret weapon storage sites; moreover, the employ space of such structures should be increased as well. A solution to this problem is using composite concrete walls [7][8][9] with a steel liner.…”
Section: Introductionmentioning
confidence: 99%